2016
DOI: 10.1111/sji.12451
|View full text |Cite
|
Sign up to set email alerts
|

Salivary and Serum Antibody Response Against Neisseria meningitidis After Vaccination With Conjugate Polysaccharide Vaccines in Ethiopian Volunteers

Abstract: Meningococcal conjugate vaccines induce serum antibodies crucial for protection against invasive disease. Salivary antibodies are believed to be important for hindering meningococcal acquisition and/or clearance of established carriage. In this study, we measured salivary IgA and IgG antibodies induced by vaccination with a monovalent serogroup A conjugate vaccine or a tetravalent A, C, W and Y conjugate vaccine, in comparison with antibody levels in serum. Saliva and serum samples from Ethiopian volunteers (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Salivary antibodies can be of systemic origin and thereby reflect levels observed in serum, or can be produced locally in mucosal tissues resulting in a lesser correlation with antibodies in serum. Our findings are in line with recent studies reporting significant correlations between IgA levels in saliva and serum [ 19 , 25 ]. However, we found lower correlation compared to those studies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Salivary antibodies can be of systemic origin and thereby reflect levels observed in serum, or can be produced locally in mucosal tissues resulting in a lesser correlation with antibodies in serum. Our findings are in line with recent studies reporting significant correlations between IgA levels in saliva and serum [ 19 , 25 ]. However, we found lower correlation compared to those studies.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies showed that parental MenCC vaccines are able to induce salivary antibodies [ 19 , 23 , 24 ]. Information about salivary responses against MenW and MenY after quadrivalent vaccination is limited [ 25 ]. The current study showed that the MenACWY-TT vaccine in adolescents elicited salivary IgA and IgG responses against MenA, MenW and MenY.…”
Section: Discussionmentioning
confidence: 99%
“…Salivary and serum correlated positively, leading to the assumption that salivary IgG derived from serum, while secretory IgA was locally produced by leucocytes, present in the gingival crevicular fluid. The same group and others [159,160] showed the same reliability of N. meningitidis serotype-specific immunoglobulin analysis from saliva, making again this sample matrix a valuable alternative in large epidemiological studies.…”
Section: Immunologymentioning
confidence: 66%
“…Due to the absence of complement in saliva, salivary antibodies are not able to kill the meningococcus, but may have an important role in prevention of attachment of meningococci to epithelial cells [2224]. Previous studies indicated that saliva IgG upon meningococcal conjugate vaccination against serogroup A, C, W and Y, rather than IgA, may be used for vaccine response monitoring because salivary IgG appears mostly serum-derived [1214, 25] and thus reflects serum IgG levels upon vaccination that correlate with serum rSBA titers. Previously, we showed a strong correlation between IgG in serum and IgG in saliva for MenC, MenW and MenY, and a lower correlation for MenA [26].…”
Section: Discussionmentioning
confidence: 99%
“…Saliva testing has previously been proposed as a potential method to monitor vaccine antibody and capsular polysaccharide antibody levels upon vaccination with conjugate vaccines, although the relationship between meningococcal salivary anticapsular antibodies and prevention of meningococcal carriage acquisition or protection against IMD is not defined [1214]. Therefore, the relation of salivary antibodies with serum SBA titers needs to be evaluated.…”
Section: Introductionmentioning
confidence: 99%